2007
DOI: 10.1007/s00296-006-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefit of radon spa therapy in the rehabilitation of rheumatoid arthritis: a randomised, double-blinded trial

Abstract: This study investigates the effects of radon (plus CO2) baths on RA in contrast to artificial CO2 baths in RA rehabilitation using a double-blinded trial enrolling 134 randomised patients of an in-patient rehabilitative programme (further 73 consecutive non-randomised patients are not reported here). The outcomes were limitations in occupational context/daily living (main outcome), pain, medication and further quantities. These were measured before the start, after the end of treatment and quarterly in the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 21 publications
1
43
0
14
Order By: Relevance
“…Although both groups showed a beneficial effect immediately after therapy, the radon group predominated significantly at the three and six months follow up. Similar results were obtained concerning cut-down in NSAID and corticosteroid intake [22]. Consistent with these findings, a previous study including 60 patients with rheumatoid arthritis clearly demonstrated pain reduction and functional improvement of affected joints after a typical regimen of thermal water baths.…”
Section: Effects Of Low-dose Radon Therapy Applied Under Hyperthermicsupporting
confidence: 88%
“…Although both groups showed a beneficial effect immediately after therapy, the radon group predominated significantly at the three and six months follow up. Similar results were obtained concerning cut-down in NSAID and corticosteroid intake [22]. Consistent with these findings, a previous study including 60 patients with rheumatoid arthritis clearly demonstrated pain reduction and functional improvement of affected joints after a typical regimen of thermal water baths.…”
Section: Effects Of Low-dose Radon Therapy Applied Under Hyperthermicsupporting
confidence: 88%
“…It should be noted, however, that the exact mechanism of the alterations in the immune function observed in this study remains unknown. Recent studies have suggested that radon in mineral water may play an important role in the relief of diseases 17,18) . However, it has also been reported that a low radon concentration failed to demonstrate a significant effect on the functioning of the endocrine system 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Of this incorporated radon, 50% disappears within 15–30 min [42], mainly through exhalation, excretion and diffusion through the skin [43,44]. The biological effects of radon are complex and may involve the release of anti- inflammatory cytokines (transforming growth factor β, interleukin 10) [45]. To the best of our knowledge there is no previous report of emerging generalized (solar) lentigines after radon exposure.…”
Section: Discussionmentioning
confidence: 99%